Tariqah in Forming the Spiritual Character of Muslim Societies - Izza Afkarina; Nur Halimah; Moh. Munthohir; Nabila Maylina; Nila Risqi Khoirun Nisa (Journal of Science and Research, 2025)
The Sufi order plays a significant role in shaping the spiritual character of Muslim communities through Sufism teachings that emphasize morality, ethics, and closeness to God. This study aims to analyze how the order contributes to the formation of individual and societal character through the practice of worship, the practice of dhikr (remembrance of God), and the development of morals. This research used qualitative methods. The results indicate that the order plays a role in strengthening spiritual values ​​such as patience, sincerity, trust (Tawakal), and compassion. Furthermore, the order also serves as a forum for the formation of social solidarity and the strengthening of Islamic identity in community life. Thus, the order not only serves as a path to individual piety but also contributes to building social harmony and improving the quality of spiritual life of Muslims.